From Pulpit to Screen: The Evolution of Islamic Scholars' Roles in the Digital Age - Syafaah, Darisy; Barizi, Ahmad; Sumbulah, Umi (Universitas Muhammadiyah Magelang, 2024)
This study investigates how the existence of religious scholars in the digital era, characterized by the dominance of new media and pop culture, influences people's understanding and practice of religion. Through qualitative research, this study shows that new media has transformed the way people access religious information and interact with religious scholars. While new media offers easier access, it also presents challenges such as the proliferation of inaccurate information and the commercialization of religion. This study highlights the importance of digital religious literacy for the public to be able to critically evaluate information circulating on social media and choose credible religious references.